B-Type Natriuretic Peptide Deletion Leads to Progressive Hypertension, Associated Organ Damage, and Reduced Survival. Issue 1 (July 2015) - Holditch, Sara J.; Schreiber, Claire A.; Nini, Ryan; Tonne, Jason M.; Peng, Kah-Whye; Geurts, Aron; Jacob, Howard J.; Burnett, John C.; Cataliotti, Alessandro; Ikeda, Yasuhiro
<x xml:space="preserve">Abstract</x> Altered myocardial structure and function, secondary to chronically elevated blood pressure, are leading causes of heart failure and death. B-type natriuretic peptide (BNP), a guanylyl cyclase A agonist, is a cardiac hormone integral to cardiovascular regulation. Studies have demonstrated a causal relationship between reduced production or impaired BNP release and the development of human hypertension. However, the consequences of BNP insufficiency on blood pressure and hypertension-associated complications remain poorly understood. Therefore, the goal of this study was to create and characterize a novel model of BNP deficiency to investigate the effects of BNP absence on cardiac and renal structure, function, and survival. Genetic BNP deletion was generated in Dahl salt-sensitive rats. Compared with age-matched controls, BNP knockout rats demonstrated adult-onset hypertension. Increased left ventricular mass with hypertrophy and substantially augmented hypertrophy signaling pathway genes, developed in young adult knockout rats, which preceded hypertension. Prolonged hypertension led to increased cardiac stiffness, cardiac fibrosis, and thrombi formation. Significant elongation of the QT interval was detected at 9 months in knockout rats. Progressive nephropathy was also noted with proteinuria, fibrosis, and glomerular alterations in BNP knockout rats. End-organ damage contributed to a significant decline in overall survival. Systemic BNP overexpression reversed the phenotype of genetic BNP deletion. Our results demonstrate the critical role of BNP defect in the development of systemic hypertension and associated end-organ damage in adulthood.